Postactivation Potentiation of the Plantar Flexors Does Not Directly Translate to Jump Performance in Female Elite Young Soccer Players - Prieske, Olaf; Maffiuletti, Nicola A.; Granacher, Urs (Frontiers in Physiology, 2018)
High-intensity muscle actions have the potential to temporarily improve muscle contractile properties (i.e., postactivation potentiation, PAP) thereby inducing acute performance enhancements. There is evidence that balance training can improve performance during strength exercises. Taking these findings together, the purpose of this study was to examine the acute effects of a combined balance and strength (B+S) exercise vs. a strength only (S) exercise on twitch contractile properties, maximum voluntary strength, and jump performance in young athletes. Female elite young soccer players (N = 12) aged 14–15 years conducted three experimental conditions in randomized order: S included 3 sets of 8–10 dynamic leg extensions at 80% of the 1-repetition maximum, B+S consisted of 3 sets of 40 s double-leg stances on a balance board prior to leg extensions (same as S), and a resting control period. Before and 7 min after exercise, participants were tested for their electrically-evoked isometric twitches (i.e., twitch peak torque, twitch rate of torque development) and maximal voluntary contraction (MVC) torque of the plantar flexor muscles. Additionally, countermovement (CMJ) and drop jump (DJ) performances (i.e., CMJ/DJ height, DJ ground contact time) were assessed. Significant effects of condition on twitch contractile properties (p < 0.05, d = 1.1) and jump performance outputs (p < 0.05, 1.1 ≤ d ≤ 1.2) were found. Post-hoc tests revealed that S compared to control produced larger PAP for twitch peak torques by trend (p = 0.07, d = 1.8, 33 vs. 21%) and significantly larger PAP for twitch rate of torque development (p < 0.05, d = 2.4, 55 vs. 43%). Following B+S compared to control, significant improvements in CMJ height (p < 0.01, d = 1.9, 3%) and DJ contact time were found (p < 0.01, d = 2.0, 10%). This study revealed protocol-specific acute performance improvements. While S resulted in significant increases in twitch contractile properties, B+S produced significant enhancements in jump performance. It is concluded that PAP effects in the plantar flexors may not directly translate to improved jump performance in female elite young soccer players. Therefore, the observed gains in jump performance following B+S are most likely related to neuromuscular changes (e.g., intramuscular coordination) rather than improved contractile properties.